2023
DOI: 10.1126/sciadv.ade8487
|View full text |Cite
|
Sign up to set email alerts
|

Plant and prokaryotic TIR domains generate distinct cyclic ADPR NADase products

Abstract: Toll/interleukin-1 receptor (TIR) domain proteins function in cell death and immunity. In plants and bacteria, TIR domains are often enzymes that produce isomers of cyclic adenosine 5′-diphosphate–ribose (cADPR) as putative immune signaling molecules. The identity and functional conservation of cADPR isomer signals is unclear. A previous report found that a plant TIR could cross-activate the prokaryotic Thoeris TIR–immune system, suggesting the conservation of plant and prokaryotic TIR-immune signals. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…And does the salvage pathway repressor NrtR distinguish between ADPR-1P and its cognate ligand ADPR 32 ? TIR domain NADases involved in cell death signaling and abortive infection produce cyclic derivatives of ADP-ribose as potent signaling molecules 18,57 . It will be interesting to test if ADPR-1P has similar properties or if RES domain phosphorylases operate on the simple logic of depleting NAD + pools.…”
Section: Discussionmentioning
confidence: 99%
“…And does the salvage pathway repressor NrtR distinguish between ADPR-1P and its cognate ligand ADPR 32 ? TIR domain NADases involved in cell death signaling and abortive infection produce cyclic derivatives of ADP-ribose as potent signaling molecules 18,57 . It will be interesting to test if ADPR-1P has similar properties or if RES domain phosphorylases operate on the simple logic of depleting NAD + pools.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the TIR-domain NLR receptors (TNLs) conferring ETI in dicot species, plants also express smaller TIR-NB and TIRonly proteins with immune-related activities [34,[113][114][115][116]. In plant transient expression assays, individual TIR domains taken from various TNLs or a natural truncated TIR-domain Resistance protein (Arabidopsis RBA1) induced cell death [34,107,108,113,117]. Tested TIRs required TIR-TIR self-association and an intact NADase catalytic site to generate NAD + hydrolysis products nicotinamide (NAM) and two cyclic ADPR variants in vitro and in vivo [107,108].…”
Section: Pathogen-activated Tnl Receptors Utilize Two CC Helo -Nlr Br...mentioning
confidence: 99%
“…The best characterized mobile and/or distally produced immune signals in plants are an induced stress metabolite, royalsocietypublishing.org/journal/rsob Open Biol. 14: 230387 N-hydroxypipecolic acid (NHP), and the biotic stress phytohormone salicylic acid (SA) [117,[150][151][152] (figure 3). Additionally, host apoplastic proteins and peptides called phytocytokines are important signals for transmission of immune and damage responses between cells and tissues [153,154].…”
Section: Nlrs Working Between Local and Systemic Immunitymentioning
confidence: 99%
“…S4, B and C). We made these mutations based on either previous studies reported or the charge and side chain of amino acid ( 50 , 51 ) (table S1). Consistent with published studies on plant TNLs, mutating two conserved residues (SH to AA) in the αA helix of CSA1 TIR from clade 2 Per-0 or clade 3 Ws-2 completely abolished CHS3-CSA1 pair–mediated cell death (Fig.…”
Section: Conserved and Clade-specific Tir Domain Features Are Require...mentioning
confidence: 99%